The impact of financial performance on workplace bullying and mistreatment in Serbian organizations - Stankov, Sanja; Poštin, Jasmina; Konjikušić, Marko; Jagodić Rusić, Aleksandra; Mićić, Daliborka (Anali Ekonomskog fakulteta u Subotici, 2020)
This paper presents the results of research into the impact of organizational financial performance items (and financial performance dimension) on workplace bullying and mistreatment. The research was conducted in organizations in Serbia, and the respondents were employees in these organizations. A total of 536 questionnaires were collected, which were valid for further analysis. The results showed that most of the observed financial performance items did not have a statistically significant impact on workplace bullying in organizations. However, the item Salaries; statistically significantly, strongly and negatively affects all observed workplace bullying dimensions and self-labelling (mistreatment) items. Thus, low employee salaries provide fertile ground for the development of workplace bullying. Conversely, with an increase in employee salaries, there is a decrease in all aspects of workplace bullying. The paper gives explanations for these phenomena. It is important for leaders and managers in business organizations to know the processes and relationships researched here. Special care should be taken in conditions of unfavourable organizational financial performance, and especially low salaries of employees.